Temporal Trends in the Association Between Female Sex and Ischemic Stroke Among Patients With Atrial Fibrillation - Mark T. Mills; Tommaso Bucci; Peter Calvert; Dhiraj Gupta; Gregory Y. H. Lip (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Female sex has historically been associated with higher risk of ischemic stroke in patients with atrial fibrillation. However, contemporary European studies suggest this association may have attenuated and become nonsignificant over recent years. This study aims to characterize temporal trends in cardiovascular outcomes in a large, global cohort of patients with atrial fibrillation. Methods Nonanticoagulated patients with newly diagnosed atrial fibrillation were identified from a global federated research network (TriNetX) between 2000 and 2019. One‐year ischemic stroke risk and risk ratios were calculated for women versus men. Secondary outcomes included all‐cause death, myocardial infarction, heart failure, and dementia. Cohorts were compared before and after adjustment for age and comorbidities. Results Overall, 1 204 852 patients were included (44% women). Unadjusted risk of ischemic stroke increased in women (1.75% to 4.24%) and men (1.13% to 3.55%) from 2000–2004 to 2015–2019, while all‐cause death decreased over the same periods (women, 10.36% to 7.79%; males, 10.76% to 7.59%). After adjustment, female sex remained independently associated with higher risk of ischemic stroke, although the risk decreased over time (2000–2004: risk ratio, 1.54 [95% CI, 0.94–2.51]; 2015–2019: risk ratio, 1.09 [95% CI, 1.06–1.13]). After adjustment, male sex was associated with risk of all‐cause death and myocardial infarction, while risk of dementia and heart failure was similar between sexes. Conclusions Between 2000 and 2019, the risk of ischemic stroke increased among nonanticoagulated patients with atrial fibrillation. While the association between female sex and ischemic stroke decreased over time, female sex remained associated with a higher stroke risk in 2015 to 2019 after adjustment.